2010
DOI: 10.4103/0250-474x.84589
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effects and safety evaluation of coumarinolignoids isolated from Cleome viscosa seeds

Abstract: The aim of the present work was to investigate the in vivo hepatoprotective potential of coumarinolignoids (cleomiscosins A, B, and C) isolated from the seeds of C. viscosa. The study was performed against CCl4-induced hepatotoxicity in albino rats. Rats were divided into four groups. The animals of group I served as normal and was given only vehicle. Group II served as toxin control and administered with CCl4 (50% solution liquid paraffin, 2 ml/kg intraperitoneally). The animals of group III received coumarin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…CLIV-92 decreased Brewerʼs yeast-induced rectal temperature and showed antipyretic activity in a dose-dependent manner in rats. These results are correlated with the earlier finding that the Cleome genus is used to cure various ailments in humans in traditional systems of medicine 23 and that the coumarinolignoids isolated from medicinal plants exhibiti anti-oxidative 24 , anti-inflammatory 25 , hepatoprotective 26 and immunomodulatory, anti-bacterial, anti-pyretic, and analgesic properties by modulating inflammation markers 27 , 28 , 29 , 30 . An acute toxicity study exhibited that a single oral dose of CLIV-92 (2000 mg/kg) did not show any significant changes in serum biochemical parameters, hematological parameters, mortality, and mobility in the experimental animals as compared to a non-treated group of animals.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…CLIV-92 decreased Brewerʼs yeast-induced rectal temperature and showed antipyretic activity in a dose-dependent manner in rats. These results are correlated with the earlier finding that the Cleome genus is used to cure various ailments in humans in traditional systems of medicine 23 and that the coumarinolignoids isolated from medicinal plants exhibiti anti-oxidative 24 , anti-inflammatory 25 , hepatoprotective 26 and immunomodulatory, anti-bacterial, anti-pyretic, and analgesic properties by modulating inflammation markers 27 , 28 , 29 , 30 . An acute toxicity study exhibited that a single oral dose of CLIV-92 (2000 mg/kg) did not show any significant changes in serum biochemical parameters, hematological parameters, mortality, and mobility in the experimental animals as compared to a non-treated group of animals.…”
Section: Discussionsupporting
confidence: 88%
“…These results are correlated with the earlier finding that the Cleome genus is used to cure various ailments in humans in traditional systems of medicine [23] and that the coumarinolignoids isolated from medicinal plants exhibiti anti-oxidative [24], anti-inflammatory [25], ▶ Table 1 Effect of CLIV-92 on carrageenan-induced acute inflammation in rats. Data are expressed as mean ± SEM: *p < 0.05; control vs. treatment; (Tukeyʼs multiple comparison test); n = 6. hepatoprotective [26] and immunomodulatory, anti-bacterial, anti-pyretic, and analgesic properties by modulating inflammation markers [27][28][29][30]. An acute toxicity study exhibited that a single oral dose of CLIV-92 (2000 mg/kg) did not show any significant changes in serum biochemical parameters, hematological parameters, mortality, and mobility in the experimental animals as compared to a non-treated group of animals.…”
Section: Discussionmentioning
confidence: 96%
“…[37][38] The liver which is the vital organ for metabolism, detoxification, and storage, possesses marker enzymes like ALT, AST, and ALP as an increase in their activities reflects active liver damage. 39 The G4 was observed to reduce the values of these marker enzymes making MOCP responsible for protecting cellular damage in conformity with similar results of Eliza et al 40 In diabetes, reduction in protein and albumin might be due to proteinuria, albuminuria, or increased protein catabolism, which are the clinical markers in diabetic nephropathy. 41 In the present study, a slight increase in G4 protein levels as compared to G3 is possible through an increase in the insulin-mediated amino acid uptake, enhancement of protein synthesis/or inhibition of protein degradation.…”
Section: Discussionsupporting
confidence: 82%
“…The plant is an important traditional medicine of the Indian-Ayurvedic and Chinese-medicine system for rheumatic arthritis, hypertension, malaria, neurasthenia, and snakebite [ 4 – 6 ]. Various scientific investigations revealed analgesic-antipyretic, anti-inflammatory, hepatoprotective, hypoglycemic, anthelmintic, and antidiarrhoeal activity of C. viscosa [ 4 , 7 – 10 ]. Panduraju et al [ 11 ] reported the topical application of C. viscosa extract accelerated the wound healing in Wistar rat with significant wound contraction rate.…”
Section: Introductionmentioning
confidence: 99%